1862 Conn. Acts 76 - (:unkn) unknown (My University, 1862)
An Act In Addition To "An Act to Provide For the Organization And Equipment Of A Volunteer Militia, And To Provide For the Public Defense," chap. 68, § 34: Required brigade inspectors to annual inspect armories and gun houses of the companies belonging to their brigades. Inspectors shall also inspect the rooms occupied by regimental bands.
Keywords: ARMED FORCES